2019
DOI: 10.2131/jts.44.811
|View full text |Cite
|
Sign up to set email alerts
|

Mild depolarization is involved in troglitazone-induced liver mitochondrial membrane permeability transition via mitochondrial iPLA<sub>2</sub> activation

Abstract: -Troglitazone, the first peroxisome proliferator-associated receptor γ agonist developed as an antidiabetic drug, was withdrawn from the market due to idiosyncratic severe liver toxicity. One proposed mechanism by which troglitazone causes liver injury is induction of mitochondrial membrane permeability transition (MPT), which occurs in a calcium-independent phospholipase A2 (iPLA 2)-dependent manner at a concentration of 10 µM. MPT, induced by opening of the MPT pore, leads to the release of cytochrome c and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Ma et al (30) reported that up-regulation of sPLA2 involved in inflammatory pathological injury to hepatopancreas caused by phoxim. Sato et al (31) revealed that enhanced decomposition of cardiolipin following mitochondrial iPLA2 activation might mediate trogitazone-induced mitochondrial membrane permeability transition.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al (30) reported that up-regulation of sPLA2 involved in inflammatory pathological injury to hepatopancreas caused by phoxim. Sato et al (31) revealed that enhanced decomposition of cardiolipin following mitochondrial iPLA2 activation might mediate trogitazone-induced mitochondrial membrane permeability transition.…”
Section: Discussionmentioning
confidence: 99%